Influences of Pagan Iconographic Types on Andalusian Plastic Works of the Early Modern Age - Porres Benavides, Jesús (Eikón / Imago, 2020)
In this article the possible influence of classical sculpture on religious sculpture in plastic works of Andalusian art is analyzed and some works especially from the Baroque period. Also the collecting of classical sculptures in early modern Spain and the possible influence of these on the sculpture of the moment is analyzed. Some specific iconographies are studied, such as the sleeping Eros and it´s possible transliteration on the theme of the sleeping baby Jesus, as well as the possible influence of Silenus with the child Dionysus on some creations of San José or the Apollo Sauroctonous in San Sebastián. Likewise, the creation of some Andalusian baroque sculptors such as Alonso Cano and Juan de Mesa and the possible use of classic fonts by both is studied.